Active surveillance for prostate cancer: can we modernize contemporary protocols to improve patient selection and outcomes in the focal therapy era?. Issue 3 (May 2015) - Tay, Kae Jack; Mendez, Melissa; Moul, Judd W.; Polascik, Thomas J.
Abstract : Purpose of review: In the absence of whole gland treatment for prostate cancer, both active surveillance and focal therapy share the common need of requiring a more thorough, detailed and precise analysis of the biological threats within the prostatic parenchyma if one chooses to monitor or selectively eradicate only specific neoplastic targets. In addition, focal therapy utilizes active surveillance post-treatment to monitor the untreated sectors of the prostate. We aim to evaluate the current modalities available to modernize active surveillance protocols in order to distinguish patients who may be safely observed from those who require intervention. Recent findings: Traditional active surveillance protocols by today's standards are rudimentary given the rapidly evolving technologies now available to clinicians. There is growing evidence for the adoption and use of multiparametric MRI and MRI-targeted biopsy to identify and localize prostate cancers of higher stage and grade. In addition, serum markers and prostate tissue DNA, RNA and methylation markers provide novel information that extends beyond Gleason grade to better characterize and define prostate cancer prognosis. Current active surveillance protocols should incorporate these modalities to improve patient stratification to surveillance, focal or whole gland interventions. Summary: Active surveillance protocols should be modernized to include cancer localization modalities and molecular prognostic markers to improve tumour characterization and better stratify men to surveillance, focal or radical intervention.